2012
DOI: 10.1115/1.4005819
|View full text |Cite
|
Sign up to set email alerts
|

Lubrication of Microelectromechanical Devices Using Liquids of Different Viscosities

Abstract: Lubrication of contacting and sliding surfaces in MEMS (microelectromechanical systems) is particularly challenging because of the predominance of surface forces at the microscale. The current paper explores the possibility of using liquid lubrication in this application. Measurements of friction and lubricant film thickness have been made for liquid lubricants of different viscosities, including low viscosity silicone oil, hexadecane, squalane, and water. Testing was carried out using a newly developed MEMS t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The two liquid lubricants tested were water and hexadecane, since these have sufficiently low viscosities to give low friction in hydrodynamically lubricated MEMS contacts [6,[8][9][10].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two liquid lubricants tested were water and hexadecane, since these have sufficiently low viscosities to give low friction in hydrodynamically lubricated MEMS contacts [6,[8][9][10].…”
Section: Methodsmentioning
confidence: 99%
“…This was initially ignored in MEMS due to the assumption that viscous drag forces would be too high [7]. However, it has been shown that liquid lubrication is effective at controlling friction and wear in MEMS, provided very low viscosity lubricants are used [8]. Furthermore, the fluid film (i.e.…”
Section: Mems Lubricationmentioning
confidence: 99%
“…Furthermore, our results suggest that 3PB experiments on intrinsic specimens could be used to identify the minimum speed for smooth cleavage during brittle fracture propagation, and that substitutional impurity content is one of the factors controlling the roughness of cleavage surfaces and, as such, should be taken into account when operatively defining the fracture toughness of crystalline specimens. At a more practical level, crystalline surface samples hosting asperities with finely controlled slope, height and spacing could be useful in experiments carried out to calibrate adhesion/friction models 31,32 , or to tune the interfacial properties that govern boundary and mixed lubrication in tribological applications in MEMS 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 summarizes the key differences between the techniques. Small scale fretting of ta-C films on Si Wear and adhesion limit the practical usability of silicon-based devices and several approaches are being considered to overcome that problem including liquid lubrication [89], solid lubrication with self-assembled monolayers [90] and a variety of thin films [91][92][93]. In [48] small scale fretting of 5, 20 and 80 nm thickness ta-C films deposited on Si(100) was investigated using spherical indenters.…”
Section: Indentation Scratch and Small Scale Fretting On Simentioning
confidence: 99%